Chemical composition of manganese nodules from the Kribati Region (CCOP/SOPAC program) - Exon, Neville F (PANGAEA, 2023)
During the evaluation of marine mineral resources of the Kiribati region sponsored by CCOP/SOPAC program (ESCAP, United Nations) various cruises of the R/V Machias successfully retrieved a number of manganese nodules. The metal contents of the nodules (dried at 105°C) were determined at the Australia. Bureau of Mineral Resources, Geology and Geophysics (BMR) using the atomic absorption method for Mn, Ni, Cu and Co, and a volumetric method for Fe.
Keywords: Geochemistry; manganese micronodule; manganese nodule; ocean; sediment